Albania : Public Expenditure and Institutional Review, Volume 2. Main Report - World Bank (Washington, DC, 2013)
This report presents an in-depth evaluation of the budgetary planning process in Albania and the institutional arrangements required for better management of public expenditures. The report does not provide a detailed analysis of expenditures or an assessment of investment projects and their outcomes in each sector. Such a shift in emphasis is appropriate given the currently weak institutional capacities in Albania and the need to enforce accountability in the public sector.The report is arranged as follows: Chapter 1 deals with the macroeconomic frmaework and policies needed to maintain fiscal sustainability and improve fiscal discipline. Chapter 2 discusses revenue and expenditure patterns, presents measures that would enhance revenue performance and analyzes the allocation of expenditures. This chapter is designed to highlight the key expenditure priorities that should be more fully addressed as Albania moves forward with the medium-term expenditure framework process (MTEF). The bulk of the report--Chapters 3, 4, and 5--addresses key challenges facing Albania to improve its institutional environment and its capacities. Chapter 3 assesses the public expenditure management process and its weaknesses and how this process should be reformed. Chapter 4 explains how establishing the MTEF mechanism could provide a better linkage between policy planning and the allocation of resources. Chapter 5 discusses meeting institutional capacity requirements.